Fine mapping of the RSC9 gene and preliminary functional analysis of candidate resistance genes in soybean (Glycine max). (26th December 2021) - Shen, Ying; Xie, Lijun; Chen, Boyu; Cai, Han; Chen, Yuanyuan; Zhi, Haijian; Li, Kai
Abstract: Soybean mosaic virus (SMV) disease is one of the main diseases affecting soybean and can cause severe soybean yield declines and seed quality deterioration. In the present study, a large F2 population (1002 individual plants) and recombinant inbred lines (RILs, 427 lines) obtained by crossing the resistant variety 'Kefeng‐1' with the susceptible variety 'NN 1138‐2' were used to fine map genes conferring resistance to the SMV strain SC9, which is common in soybean‐producing areas of Southern China. The results showed that the resistance gene RSC9 was located in a region of approximately 163 kb on chromosome 2, which is closely associated with two simple sequence repeat (SSR) markers, BARCSOYSSR_02_0610 and BARCSOYSSR_02_0618. Eleven candidate genes were included in this genomic region. Quantitative real‐time polymerase chain reaction (qRT‐PCR) analysis showed that the expression levels of seven of the 11 candidate genes differed significantly between 'Kefeng‐1' and 'NN 1138‐2'. Two of these genes with typical disease resistance domains encoding STK protein kinases ( Glyma.02g121900 and Glyma.02g122000 ) and one gene involved in an atypical disease resistance mechanism related to the ribonuclease H protein ( LOC100812666 ) were selected for further research. Tissue‐specific expression analysis showed that all three of the genes exhibited the highest expression levels in the leaves of 'Kefeng‐1'. In NN 1138‐2, Glyma.02g121900 and Glyma.02g122000 showed the highest expression in stems, and LOC100812666 showed the highest expression in roots. Subcellular localization analysis showed that Glyma.02g121900 was expressed on the cytomembrane and nuclear membrane, Glyma.02g122000 was expressed on the cytomembrane, and LOC100812666 was expressed on the cytomembrane, nucleus and mitochondria. Virus‐induced gene silencing (VIGS) reduced the expression of the Glyma.02g121900, Glyma.02g122000 and LOC100812666 genes in Kefeng‐1 by 77%, 70% and 75%, and their expression levels in 'NN1138‐2' were downregulated by 65%, 97% and 75%, respectively. After silencing these three genes in 'Kefeng‐1', only LOC100812666 ‐silenced plants exhibited significant SMV accumulation when inoculated with SMV‐SC9, with the levels being approximately seven folds higher than those in plants carrying the empty vector pBPMV‐V2. The accumulation of SMV in the SiGm2000 and SiGmLoc666 plants of NN1138‐2 inoculated with SMV‐SC9 was increased by approximately 7‐ and 13‐fold, respectively, compared with that in pBPMV‐V2 plants, but the accumulation in SiGm1900 plants was not significantly altered. Based on the above results, we concluded that Glyma.02g122000 and LOC100812666 may be involved in the conditioning of soybean resistance to SMV SC9.